ENGARUH PARTISIPASI ANGGARAN, BUDGET EMPHASIS DAN ASIMETRIS INFORMASI TERHADAP BUDGETARY SLACK DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA ORGANISASI PEMERINTAH DAERAH KOTA PEKANBARU) - , Riska Natariasari, Revi Yovita ,Rasuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine budget participation, budget emphasis and asymmetry information to budgetary slack with locus of control as a moderating variable. In this study, there was a population of 43 regional development organizations in Pekanbaru City with a sample of 20 regional development organization related to the implementation planning process and those related to budget accountability consisting of OPD heads, OPD secretaries, and finance sub-sections with the number of respondents as many as 60 people. Sampling using purposive sampling method. This research is a quantitative research. The data used in this study is primary data collected through a direct questionnaire survey with the research method used in data analysis method using descriptive statistics, data quality test, classical assumption test and hypothesis testing with the help of a computer through the SPSS 25 program. The results of the study show that budget participation, budget emphasis dan asymmetry information have a positive and significant effect on budgetary slack. The moderating variable analysis shows that the locus of control moderates asymmetry information on budgetary slack. Meanwhile, locus of control doesn’t moderate budget participation and budget emphasis on budgetary slack.The implications of this research for budget preparers are expected to able to increase their locus of control. Likewise, the government of Pekanbary City is ecpected to be able to maximize existing human resources properly to avoid budgetary slack. Keywords : Budgetary Slack, Budget Participation, Budget Emphasis, Asymmetry Information, Locus of Control